COVID-19 AND RISK INVOLVEMENT IN THE BANKING SECTOR OF BANGLADESH: A STUDY - Kumar, Dhanonjoy; Bagchi, Sraboni; Ray, Shimul (International Journal of Research -GRANTHAALAYAH, 2021)
Covid-19 pandemic has arrived at a widespread risky situation in our individual, financial and communal lives. Now the whole world is thrilled by the cruel clutch of the corona virus and its victim is the global economy. The study focuses on discovering the risk involved in Covid-19 of the banking sector in Bangladesh. Qualitative approach was used to attain the purpose of this study. The study revealed that Covid-19 has a countless effect on the economy and on the banking sector in Bangladesh. In the critical moment of , Bangladeshi banking sector faces huge financial losses, increasing non-performing loans, individual investment and decreasing operating profits. Bank employees are affected seriously for performing their daily activities. They are passing their days with great fear.